2012
DOI: 10.4028/www.scientific.net/amr.605-607.989
|View full text |Cite
|
Sign up to set email alerts
|

Structural Damage Detection of the Simple Beam Based on Responses Phase Space

Abstract: In this paper, the technology of attractor phase space in chaotic theory is introduced and applied in the structural damage detection. Firstly the phase plane is constructed with the displacement and acceleration responses. Using the changes of phase plane topology of intact and damaged responses, a new damage index is extracted, and the structural damage existence and severity are identified successfully. Since some of the state variables can not be measured, a method of phase space reconstruction is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Phase diagram analysis has gained attention for its ability to capture nonlinear dynamic characteristics associated with closed cracks. Numerous studies [ 26 , 27 , 28 , 29 ] have demonstrated the effectiveness of phase diagrams in capturing nonlinear dynamic characteristics associated with closed cracks. A careful analysis of the geometric features of the phase diagram provides valuable insights into the location and severity of closed cracks in different structures.…”
Section: Introductionmentioning
confidence: 99%
“…Phase diagram analysis has gained attention for its ability to capture nonlinear dynamic characteristics associated with closed cracks. Numerous studies [ 26 , 27 , 28 , 29 ] have demonstrated the effectiveness of phase diagrams in capturing nonlinear dynamic characteristics associated with closed cracks. A careful analysis of the geometric features of the phase diagram provides valuable insights into the location and severity of closed cracks in different structures.…”
Section: Introductionmentioning
confidence: 99%
“…The harmonic response is currently the most widely used nonlinear index [26,27], and other characteristics such as bifurcation and nonlinear strength [28,29] were also developed. The orbits in phase diagrams are sensitive to the change in mechanical properties of structures and are usually used to qualitatively analyze cracks [30][31][32], as they contain displacement and velocity information and show strongly nonlinear dynamic characteristics. Recently, phase diagrams have also been employed to quantitatively determine crack parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the proposed index is a good candidate for online health monitoring of a structure as it is sensitive to damage with less noise sensitiveness. Cheng et al 33 proposed a damage index based on the reconstructed phase space to diagnose the existence and degree of structural damage and demonstrated on a simple beam model. A damage detection approach for bridge structures under moving loads was presented by Zhang et al 34 utilising the changes in trajectory of the phase plane for multi-vibration measurements.…”
Section: Introductionmentioning
confidence: 99%